1318. Etiology of Infectious Conjunctivitis in Children: A Multi-Center Case-Controlled Study. (15th December 2022) - Frost, Holly M; Sebastian, Thresia; Jenkins, Timothy C; Keith, Amy; Kurtz, Melanie; Meece, Jennifer K; Dominguez, Samuel R; Savor-Price, Connie
Abstract: Background: Acute infectious conjunctivitis (AIC) is a common pediatric infection affecting one in eight children annually. The etiology of AIC is poorly understood but important to inform treatment and return to school recommendations. Additionally, the association of bacteria isolated from the conjunctiva with the development of clinical AIC is not well defined. We aimed to determine the bacterial and viral causes of AIC in children. Methods: Patients age 6 months-18 years with AIC at Denver Health (Denver, CO) and Marshfield Clinic (Marshfield, WI) from 2019-2021 were included. Age-matched healthy and upper respiratory infection (URI) controls without conjunctivitis were enrolled within 30 days of each case. Patients had a conjunctival flocked swab (Eswab ®, Copan Diagnostics) obtained. Nucleic acids were extracted using the NucliSENS® easyMAG® system (Quidel, San Diego, CA) per manufacturer's instructions. Multiplex RT-PCR for S.pneumoniae, H.influenzae, M.catarrhalis, S.aureus, and 11 respiratory viruses were completed using Lyra ® (Quidel, San Diego, CA) and AnDiaTec ® assay kits (Quidel Germany GmbH, Kornwestheim, Germany, Table). Nucleic acid amplification and detection was completed on the Applied Biosystems® (ABI) 7500 Fast Dx Real-Time PCR Instrument. Odds ratios were computed for each organism. Results: A total of 78 cases and 71 controls (33 healthy, 38 URI) were included (Table ). Bacteria were detected in 59 (75.6%) cases and 36 (50.7%) of controls (OR 14.3; 4.7, 33.7). Respiratory viruses were infrequently detected (cases 2, 2.6%; controls 6, 8.5%), including in the pre-pandemic period. Of bacteria detected in cases, H.influenzae was the most common (56.4%) and had the highest association with conjunctivitis (OR 11.8; 4.8, 29.1) followed by M.catarrhalis (35.9% cases, OR 2.5; 1.2, 5.3). S.pneumoniae was detected more often in controls than cases (33.8% v 26.9%). Conclusion: H.influenzae is likely the most important pathogen associated with AIC in children. Though data have suggested marginal benefit of antibiotic treat for conjunctivitis overall, studies specifically looking at benefit by organism would advance the field. A rapid diagnostic test for H.influenzae and possibly M.catarrhalis could help direct antibiotic treatment to children most likely to benefit. Disclosures: Samuel R. Dominguez, MD PhD, Biofire DIagnostics: Advisor/Consultant|Biofire DIagnostics: Grant/Research Support|DiaSorin Molecular: Advisor/Consultant|Karius: Advisor/Consultant|Pfizer: Grant/Research Support.